Some experiences with BEPCII SRF system operation - 黄彤明 林海英 孙毅） 戴建枰 王光伟 潘卫民 李中泉 马强 王群要 赵光远 米正辉 沙鹏 (Chinese physics C, 2016)
The Superconducting Radio Frequency （SRF） system of the upgrade project of the Beijing Electron Positron Collider （BEPCII） has been in operation for almost 8 years. During operation, many problems have been encountered, such as excessive heating of the power couplers, frequent beam trips during high intensity colliding, false arc interlock trigger and so on. Among them, some has been solved successfully, some have been alleviated. This paper will describe some experiences with BEPCII SRF system operation, including the symptoms, causes and solutions of problems.